The association of breastfeeding duration and language development survey score in children - Andi Faradilah; Andi Musafir Rusyaidi (Indonesian Nutrition Association, 2020)
Background and objectives: Breastfeeding is an intimate moment between mother and children. Studies had shown the effectiveness of breastfeeding to stimulate cognitive function of children including their language development. We hypothesize the longer duration of breastfeeding the higher language ability of children. This study aimed to examine the association between breastfeeding duration and LDS score of children aged 18-35 months old. Our primary outcomes were LDS-vocabulary score and LDS-phrase score. Methods: This cross sectional study was performed in 261 breastfeeding mothers with children aged 18-35 months old. A mother whose children diagnosed with delayed growth was excluded from the study. Data of breastfeeding duration (BF) and subjects’ characteristics were obtained through a questionnaire. Body mass index (BMI) of mother and weight-per age of children were collected for nutritional status. We applied language development survey (LDS) checklist form to assess vocabulary and phrase ability of the children. Statistical modelling was calculated by multiple logistic regression.Results: Prevalence of severe undernourished was highest in BF group 7-18 months vs 6 months vs >18 months old (13% vs 2% vs 4.6%, respectively). Neither LDS vocabulary nor LDS phase score have association with breastfeeding duration (p=0.973 and 0.937, respectively). Mother age, socioeconomic status, and siblingship might contribute to the association between BF duration and children language development (OR 0.63, 95% CI 0.25-1.61; OR 0.42, 95% CI 0.11-1.59, respectively).Conclusion: Breastfeeding duration is not a risk factor for delayed of children language development. This observation merits further investigation to explain the relationship between duration of breastfeeding and children language development with prospective approach.